The potential cutaneous effects of stratospheric ozone depletion - Epstein, John H. (Environmental Reviews, 1996)
Recent evidence indicates that there has been a reduction in the stratospheric ozone over the northern hemisphere, as well as the Antarctic and Arctic latitudes. This has resulted in an increased penetration of ultraviolet B (UVB) at least as measured at Toronto, Canada, since 1989. If no precautions are observed by the human population, this could eventually result in an increase in the skin cancer incidence. This would be especially true for the most common cancers, that is, the nonmelanoma skin cancers (NMSCs), basal cell carcinomas and squamous cell carcinomas. In addition it has been predicted that the third most common skin cancer, the malignant melanoma, would also increase in incidence. However, the relationship between UVB radiation and melanoma formation is much less clear than it is for NMSCs. Clinically people with a loss or lack of melanin protection such as those with occulocutaneous albinism and vitiligo, or much more commonly, people with light skin, eyes, and hair would be at greatest risk. Also increased UVB penetration could exacerbate certain infections such as herpes simplex. People with UVB-sensitive diseases including solar urticaria, polymorphous light eruptions, lupus erythematosus, dermatomyositis, pemphigus, pemphigoid, Darier's disease, familial benign chronic pemphigus, and certain recessive degenerative genodermatoses would also be potentially more vulnerable.Key words: ozone, ultraviolet B (UVB), skin cancer, photosensitive skin diseases.